DIGITIZING THE MEANING OF ENTHUSIASM IN #generasiberanipahit THROUGH MORRIS SEMIOTICS - Rini Lestari; Lieta Septiarysa; Rustono Farady Marta; Halim Agung; Fitri Murfianti (LLDIKTI Wilayah X, 2021)
The development of communication patterns carried out in virtual spaces is currently increasingly widespread. The various benefits that have been proven in various studies on digitalization efforts are driving more parties to do the same. The use of a hashtag in giving messages and impressions through digital media is one thing that should be considered. The message used needs to be structured with the right communication strategy so the series of signs, symbols, and verbal words that are used will convey the desired meaning. The hashtags of generasi berani pahit (#generatsiberanipahit) used by Jamupedia are dissected by basing the research on the constructivist paradigm and the semiotic tradition. The analytical method used is the semiotics of Charles W. Morris, which in this study focuses on the syntactic, semantic, and pragmatic dimensions. This qualitative research uses data from various scientific study literature in order to dissect and explain in detail the meaning of #generationberanipahit based on Impression Management Theory and Computer Mediation Communication Theory to get an enthusiastic attitude as a result of the meaning-making. It is also related to the philosophy of the jamu tradition, which has become the cultural wealth of Nusantara since long time ago. The enthusiastic attitude that is described by the courage to try or survive the bitter taste of jamu is also associated with the philosophy of jamu, which tells the value of life with various events that provide good and bad experiences. Good experiences are a picture of good taste, and bad experiences are the opposite.